Materials for carbon capture - Jiang, De-en, 1975-; Mahurin, Shannon; Dai, Sheng (Chemist) (John Wiley & Sons, 2020)
"As a frontier research area, carbon capture has been a major driving force behind many materials technologies. Development of advanced materials and processes for CO2 capture has a significant impact on the energy industry, society and our quality of life. Materials for Carbon Capture will cover a wide range of advanced materials and technologies for CO2 capture, reviewing the present status of the field and recent advances so that readers can better understand the challenges and opportunities. The book will discuss materials synthesis, gas separations, membrane fabrication, and CO2 removal to highlight recent progress in materials and chemistry aspects of carbon capture"--